Pengembangan Implementasi Strategi Penelitian Atas Pola Kerja Cerdas Dan Koordinasi Untuk Meningkatkan Kinerja Organisasi - . Widodo (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2009)
This study based on reserach gap strategy implementation, namely comitmment and quality communication. Contribution in this study is intervening variable smart working and coordination. The respondents for this research were the 120 executives (from a total of 526 executives) of small banking in Central Java Province. The data were then analyzed using SEM (Structural Equation Model) of AMOS. Finding result of this study indicates that strategy implementation in the efort increasing organization performance of main preference is trought smart working built trought coordination.